PENGARUH BAURAN PEMASARAN JASA TERHADAP KEPUTUSAN PELANGGAN MENGINAP DI HOTEL ASTON SAMARINDA - -, Yunita Laholo (EKONOMIA, 2015)
Consumer Perceptions of Customer Satisfaction At Aston In Samarinda .Certain factors that affect the customer to make his choice on a particular seller(partonage motive) so that he or she is using the services Aston is influenced by the equipment or adequate facilities , hospitality employees , rates or costs stay affordable and guaranteed security .In effect the person who will use certain services , not just to meet the desires and needs only (wants and needs) , but they also apply their satisfaction that a value may be obtained at the same benefits.The aim of this study are: 1. To determine the influence of the variables of service to customer satisfaction ; and 2. To determine the most dominant factor in influencing the satisfaction of the customer is staying at the Hotel Aston .The hypothesis of this study is : "It is believed that a facility services , hospitality , comfort and security , significantly influence customer satisfaction staying at Aston Samarinda Hotel " .Samples to be taken are as many as 100 people composed of 50 men and 50 women customers Aston drawn by means of purposive sampling means that the number of samples is determined by non- probability technique because the number of customers Aston can not be known with certainty .The results obtained by analysis of the form of the equation : Y = 1.309 + 0,130x1 + 0,133x2 + 0,151x3 + 0,034x4 . While the correlation ( R ) was obtained for 0.596 .From the research , it can be concluded : 1. There is a positive relationship between factors were categorized facilities , employee friendliness , comfort and security of the hotel , to customer satisfaction ; 2. H0 is rejected because there is simultaneously a significant influence factor of facilities , staff friendliness , convenience and security of the hotel , to customer satisfaction ; 3. Partial safety factor not only significantly affect customer satisfaction stay at Aston ; and 4. The convenience factor is the most dominant factor influencing customer satisfactionstay at Aston.